NIR Light‐Induced ATRP for Synthesis of Block Copolymers Comprising UV‐Absorbing Moieties - Kütahya, Ceren (John Wiley and Sons Inc., 2020)

(untitled) (Chemistry)
NIR exposure at 790 nm activated photopolymerization of monomers comprising UV‐absorbing moieties by using [Cu(II)/(TPMA)]Br(2) (TPMA=tris(2‐pyridylmethyl)amine) in the ppm range and an alkyl bromide as initiator. Some of them comprised structural elements selected either from those showing proton transfer or photocycloaddition upon UV excitation. Polymers obtained comprise living end groups serving as macroinitiator for controlled synthesis of block copolymers with relatively narrow molecular weight distributions. Chromatographic results indicated formation of block copolymers produced by this synthetic approach. Free‐radical polymerization of monomers pursued for comparison exhibited the expected broader dispersity of molecular weight compared to photo‐ATRP. Polymerization of these monomers by UV photo‐ATRP failed on the contrary to NIR photo‐ATRP demonstrating the UV‐filter function of the monomers. This work conclusively provides a new approach for the polymerization of monomers comprising UV‐absorbing moieties through photo‐ATRP in the NIR region. This occurred in a simple and efficient pathway. However, studies also showed that not all monomers chosen successfully proceeded in the NIR photo‐ATRP protocol.